Implementation of the Blue Economy Program in Achieving SDGs : An Analysis of the Impact on Natuna Coastal Communities in the 2019-2024 Period - Claudia T. Wattimena; Triesanto Romulo Simanjuntak; Novriest Umbu Walangara Nau (Badan Penerbit STIEPARI Press, 2025)
This research analyzes the implementation of the Blue Economy program in Natuna Regency to improve the welfare of coastal communities and achieve SDGs in 2019-2024. Natuna has abundant marine resources. However, the welfare level of coastal communities is still relatively low. Through a qualitative approach, this research analyzes the Blue Economy program implemented by the government by eradicating IUU fishing, developing Integrated Marine and Fisheries Centers (SKPT) that provide production, processing, and marketing facilities for marine products, including the involvement of coastal communities in decision-making and program implementation. Thus, this research is expected to evaluate Blue Economy programs and provide new insights into how these programs can be optimized to achieve economic, social, and environmental sustainability goals in Natuna and other coastal areas in Indonesia.